Effect of paddy straw based complete rations with different levels of neutral detergent fibre on microbial protein synthesis in dairy cows during early and mid lactation - CHACKO, BIJU; MOHAN, SYAM K M; ALLY, K; SHYAMA, K; ANIL, K S; SATHIAN, C T (The Indian Journal of Animal Sciences, 2017)
A study was conducted on 18 lactating dairy cows (mean milk yield, 10 kg/day) for 6 months by feeding paddy straw based complete rations containing different levels of NDF, in 2 phases, viz. early and mid lactation, to assess the microbial protein synthesis using purine derivatives (PD) excreted in urine. Isonitrogenous and isocaloric complete rations; T1, T2 and T3 with 25, 30 and 35% NDF, respectively, were formulated as per ICAR (1998). Paddy straw was the sole source of roughage NDF and the rest of was NDF met by non-forage sources, in 3 diets. PD excreted through urine was comparable between the dietary treatments, in phases I and II. The microbial protein (MBP) synthesis in T1, T2 and T3 was 997.01, 825.91 and 842.06 g, respectively, in phase I; and 1127.93, 1106.74 and 1157.24 g, respectively, in phase II. The TDN intake calculated from the values of digestibility coefficients of nutrients in T1, T2 and T3 was 5.18, 5.86 and 6.10 kg in phase I; and 8.63, 8.81 and 9.00 kg, in phase II, respectively. The efficiency of MBP production/kg of TDN was 192.47, 140.94, and 138.04 g in phase I; and 130.70, 125.62 and 128.58 g in phase II, respectively in T1, T2 and T3. Results suggested that complete diets with 25% are the most ideal NDF level in early lactation while all three NDF levels, viz. 25, 30 and 35% are ideal in mid lactation.